Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1136/jramc-2016-000632
|View full text |Cite
|
Sign up to set email alerts
|

The effect of brain tomography findings on mortality in sniper shot head injuries

Abstract: The results of this study demonstrated that pneumocephalus, midline shift, a penetrating head injury, GCS scores ≤6 and prehospital intubation are associated with high mortality, whereas patients with temporal bone fracture, perforating or single cerebral lobe head injury had a higher survival rates. The temporal bone has a relatively thin and smooth shape compared with the other skull bones so a bullet is less fragmented when it has penetrated the temporal bone, which could be a reason for the reduced cavitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…Surprisingly, the frequency of gunshot injuries in the parietal lobes of our sample was higher compared with those in the existing literature in armed personnel. 8,17 This tendency aligns with the study by Can et al, 23 who indicated that 65% of sniper head injuries during the Syrian war treated in Turkey were parietal. At the same time, both these studies on the SAC deviate from the repetitively reported dominance of frontal lobe injuries by gunshots in military personnel.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Surprisingly, the frequency of gunshot injuries in the parietal lobes of our sample was higher compared with those in the existing literature in armed personnel. 8,17 This tendency aligns with the study by Can et al, 23 who indicated that 65% of sniper head injuries during the Syrian war treated in Turkey were parietal. At the same time, both these studies on the SAC deviate from the repetitively reported dominance of frontal lobe injuries by gunshots in military personnel.…”
Section: Discussionsupporting
confidence: 86%
“…This is in line with previous studies that showed higher mortality from injuries to the brain stem and parietal lobes and injuries that pass the ventricles. 8,16,22,35 In contrast, Can et al 23 reported higher mortality in temporal injuries, which might be more specific for his sample that included only sniper head injuries. Finally, the site of injury in our sample could solely explain about 14% of the variability in mortality.…”
Section: Discussionmentioning
confidence: 79%
“…Although the mortality rate in our analysis (33.3%) excluded patients who arrived dead or died before admission, it was still signi cantly higher than in similar studies in Jordanian and Israeli centres (34,38). Meanwhile, even it is comparable to the mortality rate in the two Turkish studies, it is worth mentioning that one of them had many more patients in the severe GCS category (24), and the other recruited only gunshot injuries (21), also suggesting a worse outcome in our sample (Table 7). A possible reason for that might be the short distances and rapid transportation of victims in Damascus.…”
Section: Discussionsupporting
confidence: 61%
“…Several reports on war-related injuries in the SAC have been published in neighboring countries (20)(21)(22)(23)(24), and a systematic review found that injuries to the head, face, and neck were the most common (37%) (25). Brain damage and hemorrhage were also the most common causes of death in Syrians who presented to Turkish and Jordanian trauma centers (26, 27).…”
Section: Introductionmentioning
confidence: 99%
“…Although the mortality rate in our analysis (33.3%) excluded patients who arrived dead or died before admission, it was still significantly higher than in similar studies in Jordanian and Israeli centres [ 21 , 22 ]. Meanwhile, although it was comparable to the mortality rate in the two Turkish studies, it is worth mentioning that one of them had many more patients in the severe GCS category [ 23 ], and the other recruited only gunshot injuries [ 20 ], also suggesting a worse outcome in our sample (Table 7 ). A possible reason for that might be the short distances and rapid transportation of victims in Damascus.…”
Section: Discussionsupporting
confidence: 61%